(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This article is devoted to the neural network modeling of the drying process based on the experimental results obtained on the drying of sunflower seeds in combined drum dryer. Modeling was carried out in the Neural Networks Toolbox package in the Matlab system. The adequacy of the built model was checked and compared with the experimental results.